Validitas Modul Dasar Fashion Design Konsep Kolase pada Mata Pelajaran Dasar-Dasar Keahlian Busana Kelas X Tata Busana SMKN 2 Bukittingi - Karlina, Nora; Novrita, Sri Zulfia (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to produce learning media in the form of modules that are valid and can be used as a learning resource for students in learning collage making material. This research is research and development known as Research and Development (R&D) using the 4-D model. Modelmini has 4 stages, namely, the definition, design, development and disseminate stages. The type of data in this research is primary data. The data collection techniques used in this research were observation, interviews and questionnaires. This module was tested for validity by 4 media and material expert validators. By calculating the module assessment score from the questionnaire given and categorizing it according to the interpretation obtained. Based on the results of the material expert's validity test on the Basic Fashion Design module, a score of 93% was obtained in the very valid category, the media expert's validity test on the basic fashion design module obtained a score of 85% in the very valid category.